An Appraisal of Aṭ-Ṭabarī's Views on Allāh's Position Over the Throne (Àrsh) in His Tafsīr (Jāmicu-L-Bayān) - Abdulrasheed Mubashir Abubakar; Uthman Abdulhameed; Daud Olalekan Abdulsalam; Saheed Adewale Badmus (al-Bunyan: Interdisciplinary Journal of Qur'an and Hadith Studies, 2025)
The position of Allāh on the Throne is a theological theme that an ample written have been made on it, due to its significance in Islām. It is regarded as part of the attributes of Allāh, hence, it directly and indirectly after the faith of a Muslim. However, various explanations have been given on the meaning of this term contextually and literally from different perspectives especially the various sects in Islam. Thus, the elucidation and view of Ibn Jarīr Aṭ-Ṭabarī on this as contained in his Tafsīr will go a long way in exposing the classical view on this since his Tafsīr served as source of information for many Tafsīr. Therefore, this paper aims at appraising his view along with other theologian views in Islām. The methods that adopted in this study are historical and analytical methods of research. Historical method has been used in accounting for the biography of Aṭ-Ṭabarī, while analytical method applied in elucidating the view of Aṭ-Ṭabarī and other theologian on the topic. The findings of this paper disclose that the exegetic corpus of Aṭ-Ṭabarī views Istiwā’ as among the unseen act that Muslim should believe in. The study concluded by encouraging more research through the verses of the Qur’ān to further theological discussion especially attributes of Allāh from the view of Aṭ-Ṭabarī for better understanding.